Influence of geometrical parameters on gas-liquid intermittent flows - Escrig, Josep (2017)
The influence of geometrical parameters on the development of intermittent flow is studied in this thesis. The geometrical parameters considered are the diameter of the pipe, the angle of inclination of the pipe, and the distribution of the area of the gas injection.